Effects of throwing feints on attack strategy in male elite handball: a post-hoc video analysis - Fasold, F.; Meyer, J.; Klatt, S. (International Journal of Performance Analysis in Sport, 2023)
Previous research has attributed several performance factors for success in team handball. However, the success rate of individual attacking skill of throwing feints remains unexplored. Recent studies on other team sports show that several feinting behaviours have the potential for great success against opponents. However, there is a gap in similar studies in handball. The aim of this study was to assess relevant performance factors of throwing feints in male elite handball. We used post-hoc video analysis to investigate what kind of throwing feints (jump vs. standing throw feint) were used in elite matches (n = 90), how successful they were, and if the handedness of the players affected the use and the outcome of a throwing feint. The results show that successful throwing feints generate a notable advantage against defensive play. A greater number of jump throw feints than standing throw feints are executed and the jump throw feints showed better results. The handedness of the players only marginally influenced the effectiveness of the feints and throwing feints were used sparingly by players. Throwing feints could be a performance-relevant skill to generate an advantage against the opponent; however, further research is needed to understand why they are used so rarely.